The Effect of Tax Information Technology, Taxation System on Tax Evasion (Case Study on Individual Taxpayers in Manado City) - Lonto, Miryam Pingkan; Karongkong, Brigita Diani; Tano, Linda A. O (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
The purpose of this study is to determine how tax information technology, or the taxation system, impacts tax evasion on individual taxpayers in Manado City. All individual taxpayers operating in Manado city are included in this research population. This research uses non-probability method and uses incidental sampling technique. This study uses multiple linear regression analysis. The results showed that taxpayers' perceptions of tax evasion ethics were not influenced by tax information technology; on the contrary, the tax system had a negative and significant impact on taxpayers' perceptions of tax evasion ethics.